Somatosensitive film soft crawling robots driven by artificial muscle for load carrying and multi-terrain locomotion. Issue 6 (13th April 2021) - Liu, Zhongsheng; Zhang, Rui; Xiao, Yicheng; Li, Jiatian; Chang, Wang; Qian, Dong; Liu, Zunfeng
Abstract : Film soft crawling robot driven by twisted fiber artificial muscle for load carrying and multi-terrain locomotion. Abstract : Somatosensitive soft crawling robotics is highly desired for load carrying and multi-terrain locomotion. The motor-driven skeleton robots and pneumatic robots are effective and well-developed, while the bulk size, rigidity, or complexity limit their applications. In this paper, a somatosensitive film soft crawling robot driven by an artificial muscle was developed, which can carry heavy loads and crawl on multiple terrains. A bow-shaped film skeleton connected with a twisted-fiber artificial muscle is not easily deformed while carrying a load. A strain sensor coating on the film skeleton was used to detect the body deformation of the robot and a controller was designed for feedback control to make the robot self-crawling. This film soft crawling robot was demonstrated to crawl on the multi-terrain such as flat, mountainous, and underwater, as well as surfaces with different roughness. This work provides a new design strategy for multi-functional compact soft crawling robotics.